Development of Smart Locker System with Simultaneous User Access Capabilities for Warehouse Package Handovers - Jonathan , Michael; Hendriana, Dena; Nasution , Henry (Master Program in Mechanical Engineering, Gunadarma University, 2025)
The burgeoning of e-commerce industry especially instant delivery service provides new opportunities for warehousing companies such as PT. XYZ. However, demand for short time window in the handover process given to the warehouses is essential in the business. Piling carry-over order from previous day in combination with large incoming orders with uncontrollable user arrival time creates queues especially in the early opening hours with significant amount of the overall handover time. This research aims to develop a smart locker system tailor made for the handover purposes with fast access by the warehouse worker and simultaneous user access by scanning a dynamically generated QR Codes on each locker door. The Organic Light Emitting Diode (OLED) display could accurately show the QR Code and the locker doors could successfully open when the user scan the QR Code using the web apps. It is proven that the smart locker system could reduce the handover time with average of the package claiming time of 18.18 seconds reducing the overall handover time to below the desired 5 minutes by PT. XYZ warehouse management team.